Situation Report: Hungary, 23 June 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Inauguration of the Gyor Diesel Engine Plant Minister of Agriculture Dimeny's Visit to Holland Hungarian-Czechoslovak Contacts Hungarian-Spanish Economic Talks Hungary and East Germany Abolish Visas